An esterase-activated click and release approach to metal-free CO-prodrugs. Issue 59 (7th July 2017) - Ji, Xingyue; Ji, Kaili; Chittavong, Vayou; Yu, Bingchen; Pan, Zhixiang; Wang, Binghe
Abstract : Metal-free CO prodrugs with a biological trigger and tunable release rate are described herein for the first time. Abstract : One major challenge in the development of CO as a therapeutic agent is its controllable delivery in a pharmaceutically acceptable form. Herein, we describe for the first time a general chemical strategy to esterase-sensitive organic CO-prodrugs.